2023
DOI: 10.1002/adhm.202202949
|View full text |Cite
|
Sign up to set email alerts
|

Tumor Microenvironment Responsive Hollow Nanoplatform for Triple Amplification of Oxidative Stress to Enhance Cuproptosis‐Based Synergistic Cancer Therapy

Abstract: Cuproptosis is a recently discovered form of programmed cell death and shows great potential in cancer treatment. Herein, a copper-dithiocarbamate chelate-doped and artemisinin-loaded hollow nanoplatform (HNP) is developed via a chelation competition-induced hollowing strategy for cuproptosis-based combination therapy. The HNP exhibits tumor microenvironment-triggered catalytic activity, wherein liberated Cu 2+ catalyzes artemisinin and endogenous H 2 O 2 to produce C-centered radicals and hydroxyl radicals, r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(22 citation statements)
references
References 35 publications
0
22
0
Order By: Relevance
“…128 Elesclomol, an anticancer drug that targets mitochondrial metabolism, binds and transfers copper (Cu 2+ ) from the external environment to intracellular compartments. 129 Elesclomol is a powerful copper ionophore and stimulates copper-dependent cell death. Elesclomol precisely binds ferredoxin 1 (FDX1) and inhibits FDX1-mediated Fe–S cluster biosynthesis.…”
Section: Cuproptosis Cell Death Pathwaysmentioning
confidence: 99%
“…128 Elesclomol, an anticancer drug that targets mitochondrial metabolism, binds and transfers copper (Cu 2+ ) from the external environment to intracellular compartments. 129 Elesclomol is a powerful copper ionophore and stimulates copper-dependent cell death. Elesclomol precisely binds ferredoxin 1 (FDX1) and inhibits FDX1-mediated Fe–S cluster biosynthesis.…”
Section: Cuproptosis Cell Death Pathwaysmentioning
confidence: 99%
“…The results indicated that T-HCN@CuMS could trigger cell cuproptosis and apoptosis in the meantime. Notably, the lower protein expression level of FDX1 and LIAS in Group VI compared with Group V also hinted that reinforced oxidative stress might further amplify cuproptosis in 143B cells or perhaps augment the sensitivity of cells to cuproptosis . Meanwhile, the proportions of cuproptosis and apoptosis were also determined.…”
Section: Results and Discussionmentioning
confidence: 99%
“…Notably, the lower protein expression level of FDX1 and LIAS in Group VI compared with Group V also hinted that reinforced oxidative stress might further amplify cuproptosis in 143B cells or perhaps augment the sensitivity of cells to cuproptosis. 61 Meanwhile, the proportions of cuproptosis and apoptosis were also determined. We employed the antioxidant N-acetyl-cysteine (NAC) to eliminate ROS to better investigate the role of cuproptosis in T-HCN@CuMS-induced cell death.…”
Section: Resultsmentioning
confidence: 99%
“…Since first reported in 2022, this copper-dependent cuproptosis has sparked tremendous attention in cancer therapy and a few studies of cuproptosis-based cancer therapy have recently been reported. ,, However, the application of cuproptosis in tumor treatment suffers from several challenges: (a) the intracellular copper level was too low to realize therapeutic activity, (b) nonselectivity and potential systemic toxicity of copper ions resulted in off-target toxicities and unpredictable side effects, , and (c) there is difficulty in transporting free copper ions into cancer cells because excess copper ions were discharged out of the cells through copper exporters like ATP7A and ATP7B . Given the circumstances, increasing the copper level in cancer cells by selective delivery of exogenous copper ions was expected to promote cuproptosis and avoid potential toxicities to healthy tissues/organs. ,, Additionally, in comparison to Cu 2+ , Cu + was found to be preferable for cuproptosis because Cu + could directly bind to lipoylated TCA cycle proteins . Hence, how to deliver copper ions in the form of Cu + to cancer cells is also a concern in the development of effective cuproptosis therapy.…”
Section: Introductionmentioning
confidence: 99%